Increase in production capacity in chemical plants, with no investment in new assets - Lana, João Batista de; Marins, Fernando Augusto Silva; Muniz Junior, Jorge (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper presents the procedure used to increase the production capacity of a Chemical Industry located at São Paulo State, without new assets investment, which applies Continuous Process Improvement concepts, including Theory of Constraints (TOC) and Value Based Management (VBM). The obtained results, carried out by a team with multidiscipline skills, has been positive to the Company, with highlight, among the tangible results to an increasing of 20% in production capacity and among the intangible ones, to a better Demand and Production Planning Management Process that was implemented. Finally, suggestions and recommendations to similar applications to be well succeeded are presented. Keywords: Capacity, Theory of constraints, Value based management, Production bottleneck, Continuous improvement.